TMOD-06. LOSS OF DICER COOPERATES WITH TUMOR SUPPRESSORS TO INITIATE METASTATIC MEDULLOBLASTOMA. (1st June 2021) - Alcantara Llaguno, Sheila; Nazarenko, Inga; Chen, Yuntao; Sun, Daochun; Rocca, Gaspare La; Pedraza, Alicia; Gudenas, Brian; Saulnier, Olivier; Burns, Dennis; Bale, Tejus; Northcott, Paul; Taylor, Michael; et al.
Abstract: To determine the role of microRNA regulation in brain tumor development, we incorporated a conditional allele of the microRNA processing enzyme Dicer to a previously characterized glioma mouse model based on inactivation of the tumor suppressors Nf1, Trp53, and Pten using the Nestin-creER T2 transgene. Loss of Dicer and tumor suppressors at adult ages led to glioma development; however, mutant mice tamoxifen induced at early postnatal ages developed medulloblastoma instead of glioma. The switch in tumor spectrum occurred with 100% penetrance and tumors were histologically indistinguishable from human medulloblastoma (MB). The minimum genetic mutations required for MB formation were Dicer and Trp53. Nf1 was dispensable, while additional loss of Pten produced more invasive tumors and leptomeningeal metastases. The time window for initiation of tumorigenesis was until the 2 nd postnatal week, coinciding with the disappearance of the external granule layer (EGL), where cerebellar granule neuron precursors (CGNPs) undergo proliferation. Analysis of pre-symptomatic mutant mice showed proliferative defects and retained cells in the EGL, suggesting that the tumors may arise from CGNPs. However, targeting a subset of CGNPs using Math1-creER T2 did not lead to MB development, suggesting that an earlier EGL precursor may be required for tumorigenesis. Analysis of tumor transcriptome and MB subtype-specific genes and markers show that Dicer tumors most resemble extremely high risk p53-mutated SHH MB. Small RNA and mRNA sequencing analyses showed downregulation of microRNAs and dysregulation of its targets such as N-Myc. These studies demonstrate a role for microRNAs in MB development and show a fully penetrant genetic mouse model of highly metastatic MB.